Evaluation of ex vitro growth and field performance of micropropagated polyploid clones of Neolamarckia cadamba - Ho, Wei Seng; Shoufu, Gong; Eng, Wee Hiang; Ling, Kwong Hung (Open Science Publishers LLP, 2024)
The evaluation of field performance in tissue culture-derived seedlings is essential to determine their suitability for reforestation programs and commercial forestry, as it provides valuable insights into their adaptability to different environmental conditions and management practices. This report provides the first analysis of the growth characteristics of colchicine-induced polyploids of Neolamarckia cadamba. Field planting revealed that octoploid plants grow slower than mixoploid and tetraploid plants, but SPAD results showed that they have better photosynthetic capacity than the other two types. Notably, after 30 months of transplantation, the polyploid clones of N. cadamba exhibited better growth performance than other N. cadamba trees planted in various locations. These novel polyploid clones of N. cadamba could be valuable resources for advanced breeding programs aimed at producing improved clones for planted forest development. By enhancing the adaptability of polyploid N. cadamba clones, they have the potential to reduce the site-specific effects of N. cadamba, ultimately improving tree productivity and adaptation across different planting sites.